The Effect of Good Service to Customer Satisfaction in Lotteria Restaurant of Cibubur Bekasi Branch - Riris Lestiowati; Sudirja; M. Suwandi (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this research is to find out whether there is an influence of Excellent Service on customer satisfaction of Lottery Restaurant, Cibubur Branch, Bekasi. The method used in this research is quantitative method. Sampling in this study was taken randomly totaling 100 customers. The method used to collect quantitative data. For the calculation concept there are instrument validity tests, reliability tests, population, samples, Likert scale, correlation coefficients, determination and regression equations. Indicators or questionnaire testing of calculations using SPSS 24 Based on the calculation of the regression equation obtained equation Y = 3,742 + 0,950X, which shows that in the absence of Excellent Service, the result of Customer Satisfaction is 3,742 and if X increases or decreases by 1 or if Prime Service increases or decreases by 1% it will increase or decrease customer satisfaction by 0.950%.